ChemInform Abstract: Synthesis of Natural Products Containing Cyclohexane Units Utilizing the Ferrier Carbocyclization Reaction. Issue 48 (2nd December 2014) - Chida, Noritaka; Sato, Takaaki
Abstract Review: [40 refs.